2009
DOI: 10.1016/j.clim.2009.03.513
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the high affinity IgE receptor by neutrophils of individuals with allergic asthma is both minimal and insensitive to regulation by serum IgE

Abstract: We evaluated the hypothesis that serum IgE regulates neutrophil FcεRI expression in the same manner as described for other FcεRI + cells. FcεRI expression by neutrophils of 40 asthma subjects and 20 control subjects did not correlate with serum IgE levels, whereas FcεRI expression by basophils of the same subjects showed a highly significant correlation. The level of FcεRI expression by neutrophils of both asthma and control subjects was approximately 1% of that for basophil FcεRI expression. IgE + neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…However, a recent study reported conflicting data [21]. That is, although IgG and IgA each stimulated a concentration-dependent release of superoxide, anti-IgE antibodies did not induce superoxide production [21]. The results from the latter study agree with those of the present study in which we demonstrated that anti-IgE antibodies were unable to induce ROS production by neutrophils isolated from asthmatics sensitized with HDM allergens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a recent study reported conflicting data [21]. That is, although IgG and IgA each stimulated a concentration-dependent release of superoxide, anti-IgE antibodies did not induce superoxide production [21]. The results from the latter study agree with those of the present study in which we demonstrated that anti-IgE antibodies were unable to induce ROS production by neutrophils isolated from asthmatics sensitized with HDM allergens.…”
Section: Discussionsupporting
confidence: 89%
“…Anti-IgE antibodies have been shown to stimulate a superoxide-dependent induction of cyclo-oxygenase synthesis and activity in neutrophils [20]. However, a recent study reported conflicting data [21]. That is, although IgG and IgA each stimulated a concentration-dependent release of superoxide, anti-IgE antibodies did not induce superoxide production [21].…”
Section: Discussionmentioning
confidence: 99%
“…Increased level of IgE is a major factor in the etiology of asthma and is found abundantly in the serum of both human and murine models of asthma [25] [26] [27]. Therefore we assessed the levels of IgE in our transgenic IL-13 over-expression model.…”
Section: Resultsmentioning
confidence: 99%
“…The PBMC and normal-density granulocyte fractions were isolated as described previously. 13 Briefly, venous blood was diluted 1:1 with sterile saline (Baxter, Deerfield, Illinois) containing 4 mmol/L of ethylenediaminetetraacetic acid and was centrifuged on a 3-mL cushion of Lymphocyte Separation Medium (Lonza, Walkersville, Maryland) in a 15-mL polystyrene conical centrifuge tube for 30 minutes at 300g (4 C) with the brake off. The PBMCs were carefully collected by aspiration from the plasmaelymphocyte separation medium interface, diluted 1:3 with sterile saline, and centrifuged for 10 minutes at 250g (4 C).…”
Section: Cell Isolationmentioning
confidence: 99%
“…Normal-density granulocytes (neutrophils and eosinophils) were isolated from the granulocyteeerythrocyte pellet by 3 cycles of brief hypotonic lysis as described previously. 13 The PBMCs and granulocytes were suspended in RPMI-1640 for cell counting and then analyzed immediately by flow cytometry. Cytospin preparations of the normal-density granulocytes were prepared and treated with Wright-Giemsa stain to quantify the percentage of eosinophils, which was determined by counting at least 200 cells.…”
Section: Cell Isolationmentioning
confidence: 99%